Compounded Effervescent Magnesium for Familial Hypomagnesemia: A Case Report - Giada Bennati; Mario Cirino; Giulia Benericetti; Natalia Maximova; Monica Zanier; Federico Pigato; Anna Parzianello; Alessandra Maestro; Egidio Barbi; Davide Zanon (MDPI AG, 2023)
Familial hypomagnesemia with hypercalciuria and nephrocalcinosis (FHHNC) is a rare autosomal recessive disorder affecting <1/1,000,000 people. It is caused by mutations in the CLDN16 (FHHNC Type 1) or CLDN19 (FHHNC Type 2) genes, which are located on Chromosomes 3q27 and 1p34.2, respectively. There are no drug therapies for this condition. Although magnesium salts represent an important class of compounds and exhibit various therapeutic actions as a supplement for magnesium deficiency in FHHNC, various formulations on the market have different bioavailability. We report the case of a patient with FHNNC first treated, in our Pediatric Institute, with high doses of magnesium pidolate and magnesium and potassium citrate. The patient began to neglect this therapy after experiencing frequent daily episodes of diarrhoea. Our pharmacy received a request for an alternative magnesium supplement that would better comply by ensuring a good magnesium intake which will result in adequate blood magnesium levels. In response, we developed a galenic compound in the form of effervescent magnesium. Here, we report on the promise of this formulation not only for better compliance than pidolate, but also for better bioavailability.